The relationship and relevant factors between sleep disturbance and depressive symptoms in adolescents - Yin, Xi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Depression and sleep difficulties have a strong association. Depression may coexist with long-term sleep difficulties in some people, and vice versa for those who already have depression, they are more likely to develop sleep disturbance. In other words, the development of one symptom can trigger the development of another. Patients must therefore pay close attention to their sleep difficulties. Numerous psychiatric illnesses that are related to sleep difficulties might worsen a patient’s overall condition. If the issue of sleep difficulties is not resolved in a timely manner, it may eventually lead to the appearance of other connected psychiatric illnesses, which may make the patient’s condition worse overall. Depression is a prevalent mental illness. Clinical symptoms of depression commonly include tiredness, delayed thinking, and diminished volitional activity. Sleep disturbances can arise for a variety of reasons, including physical illnesses and psychological issues. This review can provide some suggestions for the development of prevention and intervention programs for individuals with depression and sleep disturbance.